ANALISIS PRODUK TABUNGAN WADI’AH PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH AL-FALAH BANYUASIN - Niken Sania Putri; Havis Aravik (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Sharia banking is currently on the rise and has become a reference for people to invest their funds for various needs. For this reason, various Islamic banking products must be able to be understood by the public, one of which is wadi'ah savings products. This study will discuss the analysis of Wadi'ah savings products at PT. Al Falah Banyuasin Sharia People's Financing Bank. This research is a qualitative study using primary data from direct interviews with stakeholders. The results of this study indicate that the wadi`ah principle applied to the Al Falah Banyuasin BPRS is the wadi'ah yad dhamanah which is applied to current account products. Wadi'ah dhamanah is different from wadi'ah amanah. With the two contracts carried out at the wadiah, it is possible for the depositor to get a share of the profits obtained by the deposit manager.